Essentials principles of phacoemulsification - Hasler, Pascal W. (Panamá : Japee Brothers Medical Publishers, 2013)
Cataracts are a very common condition whereby the lens of the eye becomes cloudy causing blurred vision. Over time, a cataract can get worse, eventually leading to blindness if untreated. Cataracts are the most common cause of blindness worldwide.
1. Paco methods and device settings 2. Positioning,microscope, phacodynamica and more 3. Corneal wounds 4. Capsulothexis 5 Hydrodissection and hydrodelineation
Texto en Inglés Index
Keywords: CATARATAS